ANALISIS PENGARUH KOMPETENSI DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN YANG DIMEDIASI OLEH STRESS KERJA PADA PT PELABUHAN INDONESIA IV (PERSERO) CABANG JAYAPURA - Putri Inggrid Maria Risamasu; Idayanti Nursyamsi; Wahda Rasjid (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2018)
The current organizational paradigm is toward looking at human resources as an investment that will add value to the organization not only to survive, but at the same time lead in an environment full of predictions and anticipations through an effort to create creativity and innovation of human resources). This study aims to determine the influence of competence, workload, and work stress on employee performance and how the competence and workload affect the employee performance through job stress at PT Pelabuhan Indonesia IV (Persero) Branch Jayapura. The type of research used in this study is quantitative approach. The quantitative approach bases the study of empirical rational principles. The quantitative approach bases the study of empirical rational principles. Problems and hypotheses to be tested based on defined criteria as well as path analysis tools ie Smart PLS 2.0 to know the relation of variables. The results showed that partially competence has a positive and significant effect on employee performance, work load has a positive and significant effect on employee performance, and work stress have positive and significant effect to employee performance. For indirect influence, competence and workload have a positive and significant effect on employee performance through work stress at PT Pelabuhan Indonesia IV (Persero) Branch of Jayapura.